Anteseden Agresivitas Pajak pada Perusahaan Sektor Energi yang terdaftar di Bursa Efek Indonesia - Pramesty, Anggun; Samrotun, Yuli Chomsatun (Balance: Media Informasi Akuntansi dan Keuangan, 2025)
This study aims to explore and assess tax aggressiveness influenced leverage, capital intensity, and corporate social responsibility (CSR). The research population consists of energy companies that were listed on BEI between 2021 and 2023. The sample, which consisted of 10 energy companies with 30 data points over three years, was selected via purposeful sampling. The analysis of the data was done via multiple linear regression. The results demonstrate that leverage affects tax aggressiveness whereas CSR and capital intensity do not.